Screening Allelochemical-Resistant Species of the Alien Invasive Mikania micrantha for Restoration in South China. - Ai-Ping Wu; Zi-Li Li; Fei-Fei He; Yan-Hong Wang; Ming Dong (PLoS ONE, 2015)
To screen allelochemical-resistant species of the alien invasive weed Mikania micrantha, we studied the allelopathic inhibition effects of the leaf aqueous extract (LAE) of Mikania on seed germination and seedling growth of the 26 species native or naturalized in the invaded region in South China. Seed germination was more strongly negatively affected by LAE than seedling growth. Responses of seed germination and seed growth to LAE differed differently among the target species. LAE more strongly negatively affected seed germination, but less strongly negatively affected seedling growth, in non-legume species than in legume species. LAE more strongly negatively affected seed germination and seedling growth in native species than naturalized exotic species. Therefore, naturalized exotic non-legume seedlings are more suitable than seeds of native legume species for restoration of Mikania-invaded habitats.